(3TQM GdJLQjOs - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3GdeOQSI GdeMHJg (B- (3HCUagGfs)
(3ChdgG (B:s
(3HSe Gddg (B... (3GdebUO GdKGfj aj GdLhGgQ hGdCYQGV haj aUhd ; GdChd aj GdLhGgQ bOe eHGMKgG eY eHGMK GdCYQGV dGf hLhg GdYQV eJhba Ydi hLhO GdLhgQ afGSH Pdc (B...s
(3BNQgG (B:s
... (3Ydi Tcd GdOhOI heMd GdMS GdeTJQc gh ebOe GdfXQ GdChd heMd GdNjGd eDNQI hGdMGaXI aj ebOe GdfXQ GdChd hdjS aj eDNQg JHjf agPg GdbhS (B.. (3eY GdGNJdGd(B. (3Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe , ddRQcdj (B2/227s
(3GdPQjYI (B18 ( 668)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds